PELINDUNGAN INDIKASI GEOGRAFIS GULA AREN UNTUK MENINGKATKAN PEREKONOMIAN DI DESA PAYA PINANG - Safitri, Ira; Rusnita, Ayu Novidaniati; Irshadi, Filzah; Rangkuty, Muammar Risky; Perangin-angin, Reh Bungana Beru (Jurnal Media Justitia Nusantara, 2024)
Palm sugar is very promising for its presence in the village economy if it can be managed properly, maximally, and get protection.  However, in reality the village economy has not maximally improved and has not received protection against potential geographical indications because the producers experience some obstacles in the production process and the village government pays less attention to the producers. This study aims to see and analyze the protection of geographical indications of palm sugar to improve the economy in the village of Paya Pinang. This study uses qualitative research methods with normative-empirical legal approach. Data collection using two types of data, namely primary observation and interview data. Secondary Data in the form of books, journals, and other references.  Data analysis techniques used are data reduction, data display, and data verification. The results showed that palm sugar in Paya Pinang village has a very promising economic value by requiring maximum management and must be protected so that production continues and the village economy can be further improved.